Harmonizing a Messenger Formula in Ugaritic - Watson, Wilfred G. E. 20./21. Jh. (Journal of Semitic studies, 2017)
After a brief survey of the various translations available, this note attempts to resolve some of the apparent contradictions in a formulaic passage in Ugaritic (KTU 1.3 iv 8-10 and parallels) by referring to cognate languages. The two difficult Ugaritic words for which solutions are proposed are mlḥmt and qryy.